IMPROVING EMPLOYEE PERFORMANCE AS A RESULT OF GROUP COOPERATION, WORK DISCIPLINE, AND INTERPERSONAL COMMUNICATION - Oktabella, Nancy Sophia; Setyowati, Trias; Winahyu, Pawestri (Universitas Muhammadiyah Tangerang, 2024)
The productivity of employees is impacted by the efficient execution of collective cooperation, professional conduct, and interpersonal interaction. Inherently, when these facets are effectively executed, individuals tend to demonstrate praiseworthy performance and make substantial contributions to the organization, cultivating a favorable disposition towards their job assignments. Utilizing a quantitative methodology, the study sought to ascertain relationships among these characteristics. The study encompassed an extensive sample of 119 employees, employing a saturated sample or census methodology. The findings demonstrated that the collective collaboration, exemplary conduct, and interpersonal discourse had a substantial impact on the efficacy of public servants within the regional secretariat of the Bondowoso Regency administration. Fundamentally, better collective cooperation, professional conduct, and inter-personal correspondence were found to be associated with improved and enduring staff efficiency.